The Influence of Supply Chain Performance on Batam Retail Businesses Mediated by Supply Chain Flexibility - Hay Rany; Immanuel Zai (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study analyzes the influence of supply chain performance on retail business performance in Batam City, with supply chain flexibility as a mediator. Strong supply chain performance is expected to enhance retail businesses’ ability to respond to market dynamics and consumer needs. Methodology/approach: A quantitative approach was used by distributing surveys and questionnaires to retail business actors in Batam, Indonesia. The collected data were statistically analyzed to examine the relationship between supply chain performance, supply chain flexibility, and retail business performance. Results/findings: The findings show that supply chain performance positively and significantly affects supply chain flexibility, which subsequently improves retail business performance. This confirms that supply chain flexibility plays an essential role in strengthening competitiveness and supporting sustainability. Conclusions: This study concludes that supply chain flexibility effectively mediates the relationship between supply chain performance and overall retail business success. Efficient supply chain management enables businesses to respond quickly to market changes and enhance their operational efficiency. Limitations: This study is limited to retail businesses in Batam City; therefore, the results may not fully represent other regions or sectors. Future research should broaden the scope or use longitudinal data. Contributions: This study provides empirical evidence of the importance of flexibility in supply chain management and serves as a reference for retail managers to optimize strategies for sustainable growth.